Service quality, promotion and customer satisfaction - A case of fitness centre among Gen Y in Malaysia - Chong, Sook Pei; Kua, Hui Sin; Lee, Eng Hui; Low, Jing Rou; Ong, Chen Ean (2020)
Fitness is important for people who care about their health and personal image. Fitness centres need to upgrade their services and exercise equipment constantly so that the centre can attract new consumers and in the meantime maintain current consumers. This project is examining the behaviour of a niche and profitable market: Generation Y (Gen-Y) because this group of consumers cares about their health, personal image, and self-beauty. Such assets are important to build their self-esteem, especially for public appearance. To attract and maintain the Gen-Y consumers, it’s essential for the fitness service providers to know whether the consumers are satisfied with the centre’s service quality and have reacted favourably towards the centre’s promotion. The results show that all the service quality and promotion variables are supported and thereby, on top of planning strategies that can improve the centre’s service quality, it is essential to promote incentives that are favourable to the Gen-Y.